The future of european development cooperation: Seeking global solutions or retracing a niche by 2020? - Sven Grimm; Erik Lundsgaarde (Danish Institute for International Studies (DIIS), 2009)
How EU policy for global development will look in the future depends on how the organisation manages two key challenges: The changing political dynamics within an enlarged EU with a diverse set of preferences - and the evolving external environment characterized by emphasis on global public goods and by the multiplication of global development players. These challenges put pressure on the existing European development consensus, but also offer an impetus for strengthened coordination, argue Sven Grimm and Erik Lundsgaarde.
Keywords: 330; Entwicklungskooperation; Internationale Politik; EU-Staaten